The investigation of thiol-disulfide homeostasis in patients with diabetic peripheral neuropathy - Üstün Eroğlu, Derya; Kıyıcı, Sinem; Üstündağ, Yasemin; Sığırlı, Deniz; Pekel, Nilüfer Büyükkoyuncu; Koca, Nizameddin; Emlek, Gamze; Erel, Özcan (The European Research Journal, 2022)
Objectives: Oxidative stress plays a significant role in the pathogenesis of chronic diabetic complications. Hyperglycemia induced oxidative stress is prominent for the development of diabetic polyneuropathy (PNP). Thiol disulfide homeostasis plays a vital role in antioxidant defense. In this study, we aimed to investigate thiol-disulfide homeostasis, total antioxidant capacity (TAC), and advanced oxidant protein products (AOPP) in patients with PNP. Methods: Eighty patients with T2DM and 19 healthy controls were included in the study. PNP was assessed by using the Michigan Neuropathy Screening Instrument and Electroneuromyography. TAC, AOPP, and total thiols, native thiols and disulfide levels of thiol-disulfide homeostasis parameters were studied with serum samples. The results were compared in patients with/without PNP and control group. Results: Serum HbA1c (9.5 ± 2.0% vs 8.0 ± 1.8%; p = 0.019) and triglyceride levels (204.4 ± 77.0 vs 151.7 ± 58.5 mg/dL, p = 0.014) were significantly higher and serum total thiol levels (540.4 ± 9.9 vs 566.7 ± 2.6 μmol/L, p = 0.038) were significantly lower in patients with PNP. Serum TAC, AOPP, native thiol, and disulfide levels were comparable among patients with/ without PNP. Serum CRP, AOPP, total thiol, and native thiol levels were found to be higher in patients with type 2 DM (p = 0.001, p = 0.002, p = 0.02 and p = 0.03; respectively) compared to the control group. No correlation was observed between serum thiol-disulfide homeostasis parameters and serum glucose and HbA1c levels. Conclusions: Our study reveals that oxidative stress markers such as serum TAC, AOPP, and disulfide levels are closely related to the existence of diabetes. No significant difference was noted among patients with and without diabetic PNP.